Efficiency of utilization of heat of moisture from exhaust gases of heat HRSG of CCGT - Galashov N. N. Nikolay Nikitovich; Tsibulskii (Tsibulskiy) S. A. Svyatoslav Anatolievich; Melnikov D. V. Denis Vladimirovich; Kiselev A. D. Aleksandr Dmitrievich; Gabdullina A. I. Albina Ilgizovna (2017, 2017)
Title screen